Rotavirus non-structural proteins: Structure and Function - Hu, Liya (2012)
The replication of rotavirus is a complex process that is orchestrated by an exquisite interplay between the rotavirus non-structural and structural proteins. Subsequent to particle entry and genome transcription, the non-structural proteins coordinate and regulate viral mRNA translation and the formation of electron-dense viroplasms that serve as exclusive compartments for genome replication, genome encapsidation and capsid assembly. In addition, non-structural proteins are involved in antagonizing the antiviral host response and in subverting important cellular processes to enable successful virus replication. Although far from complete, new structural studies, together with functional studies, provide substantial insight into how the non-structural proteins coordinate rotavirus replication. This brief review highlights our current knowledge of the structure-function relationships of the rotavirus non-structural proteins, well as fascinating questions that remain to be understood.